TRI HITA KARANA SEBAGAI PELESTARI SEMESTA - Warta, I Nyoman (Lembaga Penerbit Sekolah Tinggi Hindu Dharma Klaten, 2025)
The global ecological crisis characterized by environmental degradation, climate change, and biodiversity loss urges a need for holistic and sustainable alternative approaches. This paper examines Tri Hita Karana, a Balinese Hindu philosophy that offers a unique integration of spiritual, social, and ecological values ​​as a solution to environmental problems. Using qualitative methods with a cultural ecology approach, this study analyzes how the three main principles of Tri Hita Karana Parhyangan (human-God relationship), Pawongan (human-human relationship), and Palemahan (human-nature relationship)—contribute to ecosystem preservation in Bali. Parhyangan positions nature as a manifestation of the sacred Ida Sang Hyang Widhi, manifested through rituals such as Tumpek Uduh (vegetation) and Melasti (nature purification), as well as customary prohibitions (awig-awig) against the exploitation of forbidden forests. These principles instill a conservation ethic based on religious beliefs, protecting biodiversity organically. Pawongan strengthens communal collaboration in natural resource management, such as the subak system (a UNESCO-recognized traditional irrigation system) that ensures equitable water distribution and prevents ecological conflict. Meanwhile, Palemahan promotes environmentally friendly practices through traditional architecture, organic waste recycling, and coastal ecosystem restoration. The teachings of Tri Hita Karana are not only effective in maintaining Bali's ecological balance but also offer a globally relevant model of environmental ethics. However, this philosophy faces challenges from modernization, such as industrialization and mass tourism, which threaten the sustainability of local values. This suggests that integrating traditional wisdom such as Tri Hita Karana into development policies can be a transformative solution to the ecological crisis, emphasizing that humans are an integral part of, rather than masters of, the universe. These findings contribute to academic discussions on cultural ecology and sustainability, while also underscoring the importance of revitalizing local wisdom in responding to contemporary environmental challenges.